2010
DOI: 10.1126/scisignal.2000593
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of G Protein–Coupled Receptor Signaling: Specific Dominant-Negative Effects of Melanocortin 2 Receptor Accessory Protein 2

Abstract: Heterotrimeric guanine nucleotide–binding protein (G protein)–coupled receptors (GPCRs), which constitute the largest family of membrane proteins, mediate responses to diverse physiological stimuli. The presence of melanocortin 2 receptors (MC2Rs) on the plasma membrane requires the presence of either MC2R accessory protein (MRAP) or MRAP2, which are homologous accessory proteins. Here, we show that, whereas MRAP was essential for activation of MC2R signaling, MRAP2 was an endogenous inhibitor that competed wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
77
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(82 citation statements)
references
References 39 publications
4
77
1
Order By: Relevance
“…Although only the MC2 receptor requires an accessory protein, MRAP and MRAP2 both co-precipitate with all five MC receptors, and MRAP2 regulates responses of several of them, most notably the MC4 receptor involved in food intake and energy expenditure (6, 13-15, 31, 32). MRAP and MRAP2 heterodimerize readily, and MRAP2 can act in a dominant negative fashion to antagonize the effects of MRAP on the MC2 receptor (8). The results shown here raise the possibility that multiple dimers of MRAP and MRAP2 can interact with a given receptor, adding a new dimension to an already complex signaling system.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Although only the MC2 receptor requires an accessory protein, MRAP and MRAP2 both co-precipitate with all five MC receptors, and MRAP2 regulates responses of several of them, most notably the MC4 receptor involved in food intake and energy expenditure (6, 13-15, 31, 32). MRAP and MRAP2 heterodimerize readily, and MRAP2 can act in a dominant negative fashion to antagonize the effects of MRAP on the MC2 receptor (8). The results shown here raise the possibility that multiple dimers of MRAP and MRAP2 can interact with a given receptor, adding a new dimension to an already complex signaling system.…”
Section: Discussionmentioning
confidence: 74%
“…Substantial evidence indicates that MRAP forms an antiparallel homodimer (4,6,8,9). This structure is highly unusual and possibly unique among single pass membrane proteins.…”
mentioning
confidence: 99%
“…MRAP and MRAP2 are able to form heterodimeric complexes in vitro, however, whether such a complex is physiologically relevant is not known (Chan et al, 2009b;Sebag and Hinkle, 2010). In one study MC2R was expressed alongside both MRAP and MRAP2, the resulting dose response curve appeared sensitive to the ratio of MRAP to MRAP2, with increasing proportions of MRAP2 shifting the curve further to the right (Sebag and Hinkle, 2010). Importantly, this effect has not been observed in other studies (Chan et al, 2009b;Agulleiro et al, 2010).…”
Section: Mrap2 and Mc2r Signalingmentioning
confidence: 88%
“…It was suggested that this difference was due to lack of the leucine, aspartic acid, tyrosine, isoleucine (LDYI) motif in MRAP2, which was present in MRAP, and insertion of the LDYI residues enabled the MRAP2/MC2R complex to respond to lower concentrations of ACTH (Sebag and Hinkle, 2009b). MRAP and MRAP2 are able to form heterodimeric complexes in vitro, however, whether such a complex is physiologically relevant is not known (Chan et al, 2009b;Sebag and Hinkle, 2010). In one study MC2R was expressed alongside both MRAP and MRAP2, the resulting dose response curve appeared sensitive to the ratio of MRAP to MRAP2, with increasing proportions of MRAP2 shifting the curve further to the right (Sebag and Hinkle, 2010).…”
Section: Mrap2 and Mc2r Signalingmentioning
confidence: 99%
See 1 more Smart Citation